Head-Group Acylation of Chloroplast Membrane Lipids - Song, Yu (Molecules, 2021)
Head group-acylated chloroplast lipids were discovered in the 1960s, but interest was renewed about 15 years ago with the discovery of Arabidopsides E and G, acylated monogalactosyldiacylglycerols with oxidized fatty acyl chains originally identified in Arabidopsis thaliana. Since then, plant biologists have applied the power of mass spectrometry to identify additional oxidized and non-oxidized chloroplast lipids and quantify their levels in response to biotic and abiotic stresses. The enzyme responsible for the head-group acylation of chloroplast lipids was identified as a cytosolic protein closely associated with the chloroplast outer membrane and christened acylated galactolipid-associated phospholipase 1 (AGAP1). Despite many advances, critical questions remain about the biological functions of AGAP1 and its head group-acylated products.